THE CENTRAL BI-OCEANIC RAILWAY CORRIDOR (Perner's Contacts, 2021)
In this paper it is discussed the Central Bi-Oceanic Railway Corridor called as the “The Panama Canal of the 21st Century” Project that will join the Pacific and Atlantic Oceans in South America linking Brazil, Bolivia and Peru. Its impact is expected to be huge, firstly expanding trade and reducing the transport times around 30%, increasing efficiency and reducing costs.
Keywords: Bi-Oceanic; Railway Corridor; South America; Travel Time; Cost Reduction